Size effect on magnetic properties of Zn0.95-xMgxNi0.05O nanoparticles by Monte Carlo simulation - (:unkn) unknown (ELSEVIER SCI LTD, 2019)
Diluted magnetic semiconductors (DMSs) have been providing a wide research area with various conflicting results of magnetic properties which are generally originated from structural characteristics due to fabrication process. We focused on the size dependent magnetic behavior of Zn0.95-xMgxNi0.05O nanoparticles as a promising novae material introducing room temperature ferromagnetism (FM) at low doping concentrations of Mg+2 and NO(-2 )ions. Markov Chain Monte Carlo method based on Metropolis algorithm is used to simulate the system, constructed on experimental parameters such as particle size (D), lattice constants (a and c), uniaxial anisotropy constant (K), applied field (H) herewith doping concentrations of Ni (5%) and Mg (1%). However, we described the system with the Heisenberg Hamiltonian to represent the exotic nature of the DMS type materials since determining the J(ij )constants by tracing the type of the exchange relation between different types of atoms as reported in former studies. In the light of hysteresis measurements, nanoparticles generated between 5 < D < 15 nm showed strong FM among others. An exciting result is that D = 5 nm, 10 nm and 15 nm curves are so close to be overlapped. Saturation magnetization (Ms) and coercive field (H-c) had peaks of; D = 15 nm remnant magnetization (Mr) increased with increasing D up to 50 nm. Furthermore, D < 5 nm and D > 15 nm sized particles started to lose FM behavior. In addition, magnetic features of Zn0.95-xMgxNi0.05O nanoparticles can be controlled via picking a fabrication method to tune the particle size.
Keywords: Diluted magnetic semiconductor; Exchange-bias; Monte Carlo simulation; Room temperature ferromagnetism; FERROMAGNETISM